2022
DOI: 10.23887/jet.v6i2.44601
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia as a Learning Tool in Training Reading Skills of Elementary Schools Students

Abstract: Reading comprehension is a dual activity that requires various cognitive and linguistic processes to complete. This is the result of two skill sets namely: decoding and linguistic comprehension. It covers the differences in reading comprehension and provides a useful basis for classifying reading difficulties. This study aims to develop multimedia as a learning tool in training the reading skills of elementary school students. The subjects of this study involved 30 grade 5 students at the elementary school lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
0
0
Order By: Relevance
“…However, the current problem is the need for more technology-based learning media to facilitate student learning. Previous research findings also revealed teachers' difficulties developing technologybased learning media to support learning (Dewi & Sujana, 2021;Dinayusadewi et al, 2020;Siregar & Kurniati, 2022). Other findings also confirm that the lack of learning media that facilitates students impacts low student learning outcomes (Filivani & Agung, 2021;Pramestika et al, 2020;Yolanda et al, 2022).…”
Section: Introductionsupporting
confidence: 53%
“…However, the current problem is the need for more technology-based learning media to facilitate student learning. Previous research findings also revealed teachers' difficulties developing technologybased learning media to support learning (Dewi & Sujana, 2021;Dinayusadewi et al, 2020;Siregar & Kurniati, 2022). Other findings also confirm that the lack of learning media that facilitates students impacts low student learning outcomes (Filivani & Agung, 2021;Pramestika et al, 2020;Yolanda et al, 2022).…”
Section: Introductionsupporting
confidence: 53%
“…First, Android-based Lectora Inspire Media is suitable for use because it can improve student learning outcomes. Learning media is the most important thing in learning activities (Riwu et al, 2018;Siregar & Kurniati, 2022). With the Android-based Lectora Inspire media, it has a good impact on the learning process which can overcome problems in learning that often use conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Temuan sebelumnya juga mengungkapkan bahwa masih banyak guru yang kesulitan dalam merancang media pembelajaran berbasis digital (Oktarina et al, 2021;Riwu et al, 2018). Penelitian lain juga mengungkapkan bahwa masih kurangnya media pembelajaran digital yang mendukung kegiatan pembelajaran, sehingga guru harus mampu mengembangkan skill penggunaan teknologi dengan baik (Siregar et al, 2022).…”
Section: Pendahuluanunclassified